A systematic literature review of student engagement in software visualization: a theoretical perspective. Issue 2 (3rd July 2019) - Al-Sakkaf, Abdullah; Omar, Mazni; Ahmad, Mazida
ABSTRACT: Background and Context : In spite of the decades spent developing software visualization (SV), doubts still remain regarding their effectiveness. Furthermore, student engagement plays an important role in improving SV effectiveness as it is correlated with many positive academic outcomes. It has been shown that the existing SV has failed to engage students effectively. Objective : Therefore, there is a need to understand the theories behind SV design from the engagement perspective to produce a roadmap for future tool construction. The aim of this study was to identify the theories have been used in literature to explain or construct student engage- ment with SV in computer science courses for novices. Method : We performed a systematic literature review that identified a total of 58 articles published between 2011 and 2017, which were then selected for the study. However, among them, only 18 articles had discussed their theoretical framework. Findings : The results of this study show a richness in the theoretical framework obtained from different disciplines, however, constructivism is still dominant in the computing education research (CER) domain. It is evidently clear from the findings that the theories generated from the CER domain are needed to enhance the effectiveness of SV. Implications : As a result of this review, we suggest several design principles and engagement attributes to be considered while creating an engaging SV.